Guided inquiry learning model implementation to improve senior high school students’ critical thinking skills on equilibrium material - Artika Giovani; Dian Novita (Jurnal Pijar Mipa, 2022)
The study aims to improve student students' activities, critical thinking abilities, and responses toward implementing the guided inquiry learning model. The one-group pretest-posttest design was employed in the research. The research sample was 36 students from Al-Islam High School Krian Sidoarjo, West Java, Indonesia. The instruments in this research were the syllabus, lesson plans, and student worksheets. The research instruments used were the observation sheet on the implementation of the learning model, the student activity observation sheet, the pretest and posttest sheets, and the student response sheet. The research findings were: (1) The implementation of the learning model received a score of 91.11%, 94.99%, and 99.29% at meeting 1, meeting 2,  meeting 3, respectively, with very good criteria. (2) The activity of students in the first meeting was 96.23%, the second meeting was 97.40%, the third meeting was 99.11%. (3) The normality test results showed a significance value of 0.083 > 0.05, which shows that the data was normally distributed. The analysis results using the Paired Sample T-test got a significance value of 0.000 <0.05, Sig. (2-tailed) < 0.05. It indicates a significant difference between the results of the pretest and posttest. (4) The results of student responses obtained positive reactions with an average percentage of answers of 99.44%. The negative reactions with the average percentage of answers are 0.62%.